If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(F)=7F-24
We move all terms to the left:
(F)-(7F-24)=0
We get rid of parentheses
F-7F+24=0
We add all the numbers together, and all the variables
-6F+24=0
We move all terms containing F to the left, all other terms to the right
-6F=-24
F=-24/-6
F=+4
| 3n-5=n=7 | | 2.5x+6.4=3.6 | | 3/2(n+7)=5/2-n | | 8x=−128 | | 15y+27=102 | | (6x+27)=(12x+9) | | 9/5x+12=21 | | 7x+3(x-2)=14 | | 3(2m)+3)=-15 | | -5y=4y | | 3x+3=-2x+-7 | | n9=-10 | | -5y=46 | | f/4=-11 | | -9t+7=t-3 | | c+4/3+1=-7 | | -2+k=-85 | | 6.78j-5.2=4.33j+25 | | 16=-5b-3b | | 8a+96=24 | | -48=-4(4+2n) | | 35+7x=-3(3+5x) | | 14+v=-16+9v | | 2x-7=10x+9 | | 5x+4+64=180 | | 5/3q+7/3=8/5+1/3q | | -7/2u-78=-1/4 | | 7x^2-22x-60=0 | | v-15=-27 | | 4q+6=6 | | 9x-20-6x=16 | | 5x-3(4+3x)=-52 |